Analisis Pengaruh Ukuran Geometri Stripline Terhadap Kinerja BPF Mikrostrip Square Ring Resonator - Ignatius Daru Kristiadi; Dharu Arseno; Antonius Darma Setiawan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
Filter is an RF component that has an important function in a communication system. The type of filter which is usually used in receiver system is bandpass filter (BPF). The filter design method that is discussed on this paper is square ring resonator using microstrip transmission line modified by adding coupled line stub on each side of resonator. The modification is used because it is capable to optimize the return loss and to hold the insertion loss so that the filter could be working as a wideband filter. This paper discusses the influence of the geometrical changing from stripline microstrip on BPF square ring resonator microstrip performance. The evaluation is needed to obtain the optimum performance of BPF microstrip which is suitable to communication system specification. The simulation is performed using component RF simulation software with Rogers RT/Duroid 5880substrate which has dielectric constant (εr) of 2.2. The result of last simulation shows that the filter has center frequency around 1.5 GHz with its average bandwidth is around 916 MHz.